The Effect of Good Corporate Governance and Profitability On Earnings Management Pharmaceutical Companies - Faisal, Yusuf; Gumala Sari, Egi (Universitas Muhammadiyah Ponorogo, 2023)
This research aims to examine and analyze the factors that can affect of Earnings Management in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). The independent variable used to analyzed of Earnings Management is Good Corporate Governance and Profitability. This research aims at pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period. The population in this study amounted to 11 companies. The sampling method used was the purposive sampling method and obtained a sample of Â 5 companies. The data analysis method used is the multiple linear regression analysis and the residual test method. The result of this research show that simultaneously Good Corporate Governance and Profitability had positive influence and significant on Earnings Management. While, partially Good Corporate Governance and Profitability had positive influence and significant on Earnings Manegement in companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period